"Świat dziecka bez muzyki byłby pusty...." - rozważania o kulturze muzycznej dzieci = "The child`s world without music would be empty ..." - reflections on the children` musical culture - Kataryńczuk-Mania, Lidia (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The author in the article emphasises the importance of the quality of music education in the pre-school routine. Music brings cultural and cognitive values, supports the development of the child, develops his or her abilities, interests. Researches conducted by many excellent pedagogues and psychologists confirms the importance of music and the constant need for children`s musical activity. The main purpose of the article is to point out, that music should be much more appreciated in the pre-school education system.
Keywords: kultura muzyczna; edukacja muzyczna; zdolności i zainteresowania muzyczne dzieci; musical culture; musical education; musical abilities and interests of children